2022
DOI: 10.1063/5.0050312
|View full text |Cite
|
Sign up to set email alerts
|

On Wasserstein-1 distance in the central limit theorem for elephant random walk

Abstract: Recently, the elephant random walk has attracted much attention. A wide range of literature studies are available for the asymptotic behavior of the process, such as central limit theorems, functional limit theorems, and the law of the iterated logarithm. However, there is no result concerning the Wasserstein-1 distance for normal approximations. In this paper, we show that the Wasserstein-1 distance in the central limit theorem is totally different when a memory parameter p belongs to one of the three cases 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…There is a crossover phenomenon in the upper bounds at α = 0. A similar result on Wasserstein-1 distance is obtained by Ma, El Machkouri, and Fan [10]. Our main results give more precise information about such transition.…”
Section: Literature Reviewsupporting
confidence: 88%
“…There is a crossover phenomenon in the upper bounds at α = 0. A similar result on Wasserstein-1 distance is obtained by Ma, El Machkouri, and Fan [10]. Our main results give more precise information about such transition.…”
Section: Literature Reviewsupporting
confidence: 88%
“…In the critical regime, we have (n log n) −1/2 S n → N (0, 1) in distribution and n 1−2p S n → L almost surely and in L 4 in the superdiffusive regime. The reader can refer to Baur and Bertoin [1], Bercu [2,3], Bercu and Laulin [4], Coletti et al [5], Laulin [11] and the references their in and to Ma et al [12] and Dedecker et al [6] for contributions to the rate of convergence in the central limit theorem of the ERW. Since the seminal paper by Schütz and Trimper [13], many variants of the ERW where introduced in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest that there is a transition of the convergence rate at p = 1/2. However, the results obtained in [7,8] are about the change of upper bounds for the accuracy of the normal approximation. This motivates the study in the current paper.…”
Section: Introductionmentioning
confidence: 92%
“…The main interest of the study of the ERW is to investigate the long term memory effects. In [1], it is shown that the ERW exhibits both normal and anomalous (super) diffusion, depending on the memory parameter p. Last few years, many authors have studied several limit theorems describing how the memory influences the asymptotic behavior of the ERW (see [2][3][4][5][6][7][8][9] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation